Barriers facilitators and needs of female sex workers in Arak to access sexual health services a qualitative study - Iman Navidi; Elham Shakibazadeh; Firoozeh Raisi; Samaneh Akbarpour (Scientific Reports)
Abstract The sexual health of female sex workers is of particular concern due to severe complications arising from multiple and unprotected sexual relationships. This qualitative study, the initial study conducted in Iran, explored the sexual health needs, barriers, and facilitators to accessing sexual health services among women at high risk of STIs in Arak. In this qualitative research study, we used a content analysis design. Fourteen female sex workers who attended the specialized HIV center in Arak participated in the study. Data were collected and analyzed using qualitative content analysis. Data were classified into three main themes: (1) barriers and facilitators in accessing sexual health services; (2) educational needs for sexual health; and (3) peer education from the perspectives of sex workers. Three categories of barriers emerged: “personal”, “environmental and structural”, and “psychological and social” ones. Personal barriers included a lack of information, privacy concerns, fear of untreatable or complex diagnoses, and cultural beliefs and shame. Environmental and structural barriers included financial barriers, inadequate emphasis on sexual health, mistreatment by healthcare staff, poor quality of distributed condoms, and insufficient preventive education. Psychological and social barriers included partner rejection following infection. Facilitators for accessing sexual health services included respectful care, effective counseling for anxiety and stress. Access to preventive healthcare included the availability of screenings and vaccinations, and condom distribution at the center. Educational needs encompassed skills in negotiation and communication, understanding sexual health, positive body image and accepting sexual orientation, and preventing and managing STIs. The participants believed that peer education offers several benefits, including building credibility and trust among peers, fostering positive interactions within peer groups, enhancing support through shared experiences, improving access to educational resources and empowerment through peer education. However, it also presented drawbacks, such as a lack of trust in peers and deficiencies in specialized resources. To improve access to sexual health services for female sex workers, it is essential for services to be transparently and comprehensively introduced; and for cultural and social barriers to be reduced. Additionally, it is recommended that services be provided either free of charge or at reduced costs to enable this vulnerable group to utilize the services effectively. Future studies should focus on investigating strategies to gather data and improve sexual health of female sex workers at community level.